SELF-DECEPTIVE RESISTANCE TO SELF-KNOWLEDGE - Hubbs, Graham (Les ateliers de l'éthique / The Ethics Forum, 2018)
Philosophical accounts of self-deception have tended to focus on what is necessary for one to be in a state of self-deception or how one might arrive at such a state. Less attention has been paid to explaining why, so often, self-deceived individuals resist the proper explanation of their condition. This resistance may not be necessary for self-deception, but it is common enough to be a proper explanandum of any adequate account of the phenomenon. The goals of this essay are to analyze this resistance, to argue for its importance to theories of self-deception, and to offer a view of self-deception that adequately accounts for it. The view’s key idea is that, in at least some familiar cases, self-deceived individuals maintain their condition by confusing a nonepistemic satisfaction they take in their self-deceived beliefs for the epistemic satisfaction that is characteristic of warranted beliefs. Appealing to this confusion can explain both why these self-deceived individuals maintain their unwarranted belief and why they resist the proper explanation of their condition. If successful, the essay will illuminate the nature of belief by examining the limits of the believable.